2015
DOI: 10.3389/fphar.2015.00058
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives in signaling mediated by receptors coupled to stimulatory G protein: the emerging significance of cAMP efflux and extracellular cAMP-adenosine pathway

Abstract: G protein-coupled receptors (GPCRs) linked to stimulatory G (Gs) proteins (GsPCRs) mediate increases in intracellular cyclic AMP as consequence of activation of nine adenylyl cyclases , which differ considerably in their cellular distribution and activation mechanisms. Once produced, cyclic AMP may act via distinct intracellular signaling effectors such as protein kinase A and the exchange proteins activated by cAMP (Epacs). More recently, attention has been focused on the efflux of cAMP through a specific trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 95 publications
1
40
0
Order By: Relevance
“…Gas is known to induce cAMP by activating adenylate cyclase (Godinho et al, 2015). Gai can contribute in inducing cytosolic Ca 2+ and in suppressing cAMP levels (Chow and Davis, 2000; Lee et al, 2007; Scott et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Gas is known to induce cAMP by activating adenylate cyclase (Godinho et al, 2015). Gai can contribute in inducing cytosolic Ca 2+ and in suppressing cAMP levels (Chow and Davis, 2000; Lee et al, 2007; Scott et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that extracellular cAMP could function via G protein-coupled receptors (GPCRs) on basal gut membranes to induce invagination. cAMP can activate GPCRs directly (Miranda et al, 2015) or can first be metabolized extracellularly to adenosine (Godinho et al, 2015). In Dictyostelium development, cAMP secreted by ABC transporters stimulates chemotaxis (Miranda et al, 2015), and chemotaxis is an important mechanism of cell movement during deuterostome gastrulation (Dormann and Weijer, 2006).…”
Section: How Does C5a In Pigment Cells Affect the Position Of The Hinmentioning
confidence: 99%
“…Regarding the intracellular mechanism of incretins, the specific receptors for GIP or GLP-1, which belong to GTP-binding protein-coupled receptors, couple to adenylyl cyclase-activating Gs, leading to the production of cAMP (23). With regard to osteoblasts, it has been reported that both GIP and GLP-1 truly increase the intracellular cAMP levels (15).…”
Section: Discussionmentioning
confidence: 99%